Preparation of sludge-based activated carbon and its application for phosphorus adsorption - HE Zishuai; LI Haitao; GAO Hong (Gongye shui chuli)
Dehydrated sludge and digested sludge were used as raw materials, ZnCl2, H2SO4 and KOH were used as activators to prepare sludge biochar, with iodine adsorption value as the evaluation index. The results showed that the dehydrated sludge biochar(TSAC) and digested sludge biochar(XHAC) prepared with ZnCl2 as activator had the highest iodine adsorption values of 355.1 mg/g and 289.2 mg/g, respectively. TSAC and XHAC were applied to phosphorus containing wastewater and compared with commercial activated carbon(CAC). The effects of adsorption time,dosage, and pH on phosphorus adsorption were investigated, and the chemical forms and ecological risks of heavy metals in sludge and TSAC were analyzed. The adsorption mechanism was explored with SEM, XRD, FT-IR, and BET. The results showed that when the adsorption time was 360 min and pH of 6, the adsorption capacity of TSAC and XHAC for phosphorus was 7.3 mg/g and 6.8 mg/g, which was higher than the adsorption capacity of commercial activated carbon(4.1 mg/g). The adsorption process conformed to the Langmuir model and pseudo second-order kinetic equation, and was a chemical adsorption on the surface of a single molecular layer. The potential ecological risk of heavy metals in TSAC was low, while that for sludge was medium, which indicated that the morphological stabilization of heavy metals could be achieved by preparing sludge activated carbon from pyrolysis sludge.